2021
DOI: 10.31244/jero.2021.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Destination-language acquisition of recently arrived immigrants: Do refugees differ from other immigrants?

Abstract: This article describes new immigrants’ levels of destination-language proficiency shortly after taking up residence in Germany. The focus lies on a comparison of refugees from Syria with new arrivals from Italy, Poland, and Turkey, who came as economic immigrants, for family reasons, or as students. The theoretical account builds upon a well-established model of language acquisition, according to which language fluency is a function of exposure, efficiency, and incentives. The empirical study is based on data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Poor mental health can in turn hamper the efficiency of language learning (Chiswick and Miller 2001;van Tubergen and Kalmijn 2005). However, studies addressing refugees' language acquisition thus far have not found evidence supporting this line of reasoning (Kristen and Seuring 2021;van Tubergen 2010;Hunkler and Khourshed 2020).…”
Section: Application To Recent Refugees and Other New Immigrantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Poor mental health can in turn hamper the efficiency of language learning (Chiswick and Miller 2001;van Tubergen and Kalmijn 2005). However, studies addressing refugees' language acquisition thus far have not found evidence supporting this line of reasoning (Kristen and Seuring 2021;van Tubergen 2010;Hunkler and Khourshed 2020).…”
Section: Application To Recent Refugees and Other New Immigrantsmentioning
confidence: 99%
“…Considering that schools also train individuals in how to acquire new skills, refugees who have received very little formal education may be less prepared to acquire the destination language. While individuals who cannot read and write are virtually nonexistent in other recent immigrant populations, the least educated segments among recent refugees include considerable numbers of illiterate individuals (Kristen and Seuring 2021;UNESCO 2020;Brücker, Rother, and Schupp 2017, 47). 4 For this reason, learning patterns may also differ between refugees and other new immigrants.…”
Section: Application To Recent Refugees and Other New Immigrantsmentioning
confidence: 99%
See 3 more Smart Citations